All Wales Injury Surveillance System revised: development of a population-based system to evaluate single-level and multilevel interventions. (9th December 2015) - Lyons, Ronan A; Turner, Samantha; Lyons, Jane; Walters, Angharad; Snooks, Helen A; Greenacre, Judith; Humphreys, Ciaran; Jones, Sarah J
Abstract : Background: Injury surveillance has been established since the 1990s, but is still largely based upon single-source data from sentinel sites. The growth of electronic health records and developments in privacy protecting linkage technologies provide an opportunity for more sophisticated surveillance systems. Objective: To describe the evolution of an injury surveillance system to support the evaluation of interventions, both simple and complex in terms of organisation. Methods: The paper describes the evolution of the system from one that relied upon data only from emergency departments to one that include multisource data and are now embedded in a total population privacy protecting data linkage system. Injury incidence estimates are compared by source and data linkage used to aid understanding of data quality issues. Examples of applications, challenges and solutions are described. Results: The age profile and estimated incidence of injuries recorded in general practice, emergency departments and hospital admissions differ considerably. Data linkage has enabled the evaluation of complex interventions and measurement of longer-term impact of a wide range of exposures. Conclusions: Embedding injury surveillance within privacy protecting data linkage environment can transform the utility of a traditional single-source surveillance system to a multisource system. It also facilitates greater involvement in the evaluation of simple and complex healthcare and non-healthcare interventions and contributes to the growing evidence basis underlying the science of injury prevention and control.